Design of an 10 kVA-45 A automatic static transfer switch module - Noel, Julien George Andre (2014)
Uninterruptible Power Supplies (UPS’s) are designed to provide emergency power when the main power source fails. To avoid this impact and to protect effectively the loads, one solution is to provide a redundant loading system using a dual power energy source other than the UPS to achieve an automatic static transfer when necessary. In this work, an additional module has been designed and connected between a critical load and the output of two independent UPS systems; if primary UPS fails, the module automatically transfers the load to the other one with a minimum transfer switching time. The results presented demonstrate a transfer switch time below 3 ms, compared to commercial products of 4 to 6 ms.